Performance of nitrification inhibitors with different nitrogen fertilizers and soil textures. Issue 5 (21st May 2019) - Barth, Gabriel; von Tucher, Sabine; Schmidhalter, Urs; Otto, Rafael; Motavalli, Peter; Ferraz-Almeida, Risely; Meinl Schmiedt Sattolo, Thales; Cantarella, Heitor; Vitti, Godofredo Cesar
Abstract: Nitrification inhibitors (NIs), DCD (dicyandiamide), and DMPP (3, 4‐dimethylpyrazole phosphate), in combination with urea (UR) and ammonium sulfate nitrate (ASN) fertilizers were studied under contrasting soil textures (sand, loam, and clay) from cultivated soils collected in Brazil and Germany. Soil samples were incubated over 50 days and the content of ammonium ( N - NH 4 + ), nitrate ( N - NO 3 - ), and soil pH were measured periodically. Applied NIs delayed the nitrification process across all soil textures. Correlation analysis indicated that combining ASN with NIs resulted in higher NH 4 + content and efficiency in delaying the nitrification process with high N‐conversion rate ( r = –0.82). The combination of ASN+ DMPP increased the efficiency of the N‐conversion rate ( r = –0.86) due to H + release in soil, while UR+DCD ( r = –0.50) had an efficiency of the N‐conversion rate similar to UR ( r = –0.42). All the NIs had a better performance in reducing N - NO 3 - formation in sandy soils as compared to the loam and clay textured soils. Use of DMPP with an N fertilizer results in a soil pH decrease and can be an option to increase the efficiency of the N‐conversion rate, reducing N losses in soil. Overall, our results suggest that NIs have a better performance in reducing N - NO 3 - formation in sandy soils as compared to that of the loam and clay textured soils. Use of DMPP with ASN results in a soil pH decrease and can be an option to reduce N losses in soil.